2022
DOI: 10.5933/jkapd.2022.49.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relationship between Sella Turcica Morphology and Delayed Dental Age

Abstract: The purpose of this study was to evaluate the relationship between sella turcica morphology and delayed dental age. In total, 389 participants under 16 years old were selected. Dental age was evaluated by the Demirjian method and age discrepancy (AD), the value subtracted from dental age to chronological age, was calculated. The participants were divided into 8 groups based on the sella turcica type. Bridging ratio (BR) was defined as interclinoid distance divided by sella turcica length to determine the degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Corresponding to this result, the number of males who visited pediatric dentistry was higher than that of females over the past 11 years, and the sex distribution of patients who underwent sedation also reflected this. Additionally, according to a study by Choi and Park in 2003, males showed higher anxiety than females in a dental environment, and according to a study by Boyar and Cross in 1997, the behavioral patterns of males before separation from their parents were worse than those of females [ 17 18 ]. Based on these results, it can be said that in the case of males, patients and dentists tend to prefer sedation.…”
Section: Discussionmentioning
confidence: 99%
“…Corresponding to this result, the number of males who visited pediatric dentistry was higher than that of females over the past 11 years, and the sex distribution of patients who underwent sedation also reflected this. Additionally, according to a study by Choi and Park in 2003, males showed higher anxiety than females in a dental environment, and according to a study by Boyar and Cross in 1997, the behavioral patterns of males before separation from their parents were worse than those of females [ 17 18 ]. Based on these results, it can be said that in the case of males, patients and dentists tend to prefer sedation.…”
Section: Discussionmentioning
confidence: 99%
“…The current study found that high vowel contexts were more sensitive to temporal aspects of nasalization than low vowel contexts. Similarly, Cho et al [28] emphasized that high vowel contexts had more significant nasalization components than low vowel contexts [28]. Moreover, Kulak Kayikci and Ozgen [29] organized Turkish vowel contexts from high to low according to the mouth structures of 10 healthy adults using magnetic resonance imaging as follows: /i/, /ü/, /e/, /u/, /ı/, /ö/, /o/, and /a/.…”
Section: Temporal Aspects Between Groupsmentioning
confidence: 99%